Quantifying aviation's contribution to global warming. (4th November 2021) - Klöwer, M; Allen, M R; Lee, D S; Proud, S R; Gallagher, L; Skowron, A
Abstract: Growth in aviation contributes more to global warming than is generally appreciated because of the mix of climate pollutants it generates. Here, we model the CO2 and non-CO2 effects like nitrogen oxide emissions and contrail formation to analyse aviation's total warming footprint. Aviation contributed approximately 4% to observed human-induced global warming to date, despite being responsible for only 2.4% of global annual emissions of CO2 . Aviation is projected to cause a total of about 0.1 °C of warming by 2050, half of it to date and the other half over the next three decades, should aviation's pre-COVID growth resume. The industry would then contribute a 6%–17% share to the remaining 0.3 °C–0.8 °C to not exceed 1.5 °C–2 °C of global warming. Under this scenario, the reduction due to COVID-19 to date is small and is projected to only delay aviation's warming contribution by about five years. But the leveraging impact of growth also represents an opportunity: aviation's contribution to further warming would be immediately halted by either a sustained annual 2.5% decrease in air traffic under the existing fuel mix, or a transition to a 90% carbon-neutral fuel mix by 2050.